Women in the Parliament of Uganda, 2001 - 2009 : the socio- economic and political profiles and their impact on policy outcome - Juma, Kakuba Sultan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
The purpose and overall objective of this study is to identify and establish the association between the social, economic and political profiles of woman Members of Parliament who served in the 7th and 8th Parliaments of Uganda and their legislative roles performance; explore the pro-woman issues they raised and establish corresponding policy outcome on these issues. Thus, the study combines both the quantitative and qualitative results obtained from secondary and primary sources. The primary sources were mainly Hansards, Members of Parliament Directory, Parliamentary attendance logbook and interviews. Meanwhile, the secondary sources were textbooks, journals, newspapers and other published and unpublished materials related to the study. Two methods of data collection were used i.e. content analysis and interviews. One-on-one separate semi-structured interviews were conducted with a total of 16 woman Members of Parliament, while content analysis was used to treat data obtained from Hansards, Parliamentary Directory and attendance logbook. A total of 377 Hansards were selected out of the 752 using systematic sampling. The data generated from Hansards were particularly on legislative roles performance and policy outcome. Meanwhile, data on social, economic and political profiles were generated from Members of Parliament Directory. These data were analyzed with the help of Statistical Package for Social Sciences, particularly the Chi Square/Fisher's Exact to establish the relationship between social, economic and political profiles and legislative roles performance and, legislative roles performance and policy outcome. The findings reveal that there was a significant association between education and all the constructs of legislative roles performance, while the relationship between other social, economic and political variables and the constructs of legislative roles performance varied. The results also reveal that women in the Parliament of Uganda in their legislative roles performance, succeeded in influencing the Parliament to enact pro-women legislations such as Domestic Violence Act and Female Genital Mutilation Act. The conclusion is that the women's legislative roles performance cannot be explained in isolation from their social, economic and political backgrounds. These variables seem to have a bearing on their legislative roles performance, such as introducing and debating women issues in the parliament among other legislative roles performance. This has helped them to influence legislations, which are important in promoting woman related issues and to protect the status of women in Uganda.